Examining Organizational Culture and Employee Performance: The Case of the Auditor General's Office, Zambia - Mwambwa, Ron M.; Asif, Mahbub Karim; Hock, Oo Yu; Nadia, Farhana (2020)
This study investigated the influence of the Annual Performance Appraisal System (APAS) on employee performance in the Office of the Auditor General (OAG) of Zambia. Specifically, the study focuses on whether organizational culture has an effect on employee performance in the OAG despite the implementation of the Annual Performance Appraisal System. The study used a mixed method approach to collect and analyse data. The results of the study showed that organizational culture can influence employee performance despite implementation of an annual performance appraisal system. The implications of the results reiterate the value of re - designing the APAS so that it takes into account factors such as organizational culture that currently affect its influence on enhancing employee performance in the OAG.